The Role of Qur'anic Exegesis in Promoting Social Welfare: A Literature Review of The Implementation of Justice Values in The Holy Verses - Anshara, Jessenia Hayfa; Nurrohim, Ahmad (Universitas Muhammadiyah Surakarta, 2023)
The Role Of Quranic Exegesis In Promotion Social Welfare: A Literature Review Of The Implementation Of Justice Values In The Holy Verses. The Quran, as the primary guide in Islam, encompasses practical and spiritual guidance for daily life. This study focuses on the role of the interpretation (tafsir) of the Quran in enhancing social well-being, with a specific emphasis on the values of justice embedded in the sacred text. The research aims to describe the role of Quranic interpretation in improving justice and social well-being, contributing to a deeper understanding of the practical implementation of justice values in daily life based on Islamic teachings. The study employs a literature review approach to analyze scholars' interpretations of Quranic verses related to justice and social well-being. The literature review involves a profound understanding of various interpretations to illustrate the relationship between Quranic interpretation and justice values. The impacts include the formation of a more just society, enhanced moral character, and increased awareness of social issues. Quranic interpretation plays a crucial role in guiding the implementation of justice values to enhance social well-being. Despite challenges, involving the community through education and leveraging the role of religious leaders can be key to overcoming obstacles. By identifying and leveraging these opportunities, it is expected that the implementation of justice values based on Quranic interpretation can have a positive impact on society.